THE EFFECT OF ZAKAT ON THE CONSUMPTION OF MUSTAHIK HOUSEHOLDS (A STUDY OF ZAKAT RECIPIENTS FROM BAZNAS IN PROBOLINGGO CITY) - Nurlita, Elok; Ekawaty, Marlina (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2017)
This article aims to analyze the effect of zakat directly and indirectly on household consumption of mustahik. The approach of this research is quantitative. Data obtained from 50 mustahik (receiver of zakat) BAZNAS Probolinggo Municipality with Proportional Random Sampling method and analyzed by Path Analysis. The results showed that zakat and the number of household members directly and indirectly affect the household consumption of mustahik. Furthermore, household income as an intermediate variable also affects the household consumption of mustahik, whereas education and age have no effect on the household consumption of mustahik, either directly or indirectly.Keywords: Poverty, Consumptive Zakat, Productive Zakat, Household Consumption, BAZNAS Probolinggo Municipality.